BET & ELF Quantum Topological Analysis of Neutral 2-Aza-Cope Rearrangement of γ-Alkenyl Nitrones - Merino, Pedro (Molecules, 2017)
The 2-Aza-Cope rearrangement of γ-alkenyl nitrones is a rare example of the neutral thermal 2-aza-Cope process that usually takes place with cationic species. During the rearrangement, a redistribution of bonds and electronic density occurs in one kinetic step. However, the introduction of substituents with different steric requirements and electronic features might alter the activation energies and the synchronicity of the reaction. The electron localization function (ELF) analysis and its application to Bonding Evolution Theory (BET) analysis within the context of Molecular Electron Density Theory (MEDT) is an excellent tool to monitor the electron density along the reaction coordinate and thus investigate in detail bond breaking and formation and the corresponding energy barriers. By analyzing topological ELF calculations of seventeen 2-aza-Cope nitrone rearrangements with selected substituents, the main factors influencing the synchronicity of the process were investigated. This MEDT study results revealed that the rearrangement is a non-polar process mostly influenced by steric factors rather than by electronic ones, and confirms the pseudoradical character of the process rather than any pericyclic electron-reorganization.